2014
DOI: 10.1103/physreve.90.042924
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational higher-order resonances in an overdamped bistable system with biharmonic excitation

Abstract: Experimental evidence of vibrational higher-order resonances in a bistable vertical-cavity surface-emitting laser driven by two harmonic signals with very different frequencies is reported. The phenomenon shows up in a parameter space (the dc current, the amplitude of the high-frequency signal) as well-defined structures with multiple local maxima at higher harmonics of the low-frequency signal. Such structures appear due to a strong suppression of higher harmonics for certain values of the high-frequency ampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 25 publications
2
19
0
Order By: Relevance
“…Through a different combination of p, m and n, we can get the superharmonic frequency components such as 2ω, 3ω, 4ω, 5ω, etc., in the response. This prediction has been verified in [12,13]. If we consider the subharmonic resonance in Eq.…”
Section: Introductionsupporting
confidence: 57%
See 3 more Smart Citations
“…Through a different combination of p, m and n, we can get the superharmonic frequency components such as 2ω, 3ω, 4ω, 5ω, etc., in the response. This prediction has been verified in [12,13]. If we consider the subharmonic resonance in Eq.…”
Section: Introductionsupporting
confidence: 57%
“…The VSupR at the superharmonic frequency nω where n is a positive integer and n > 1 has been reported in [12] and [13]. However, based on the analysis in Sec.…”
Section: Vibrational Superharmonic Resonancementioning
confidence: 97%
See 2 more Smart Citations
“…Such amplification takes place when the response amplitude becomes minimum at the bifurcation of the effective potential. Following the foundational studies on VR [11,13,15], vibrational resonance has attracted a lot of research attention and has been reported in bistable systems [11,15,19], multistable systems [20][21][22], excitable systems [23], ratchets [24], quintic oscillators [25], overdamped systems [11,21,24], coupled oscillators [21,26], delayed systems [21,[26][27][28], asymmetric Duffing oscillators [29], fractional order damped oscillators [30][31][32], feedback networks [33], neuron models [23,34,35], a synthetic gene network [36], biological nonlinear maps [37], and systems with nonlinear dissipation [38][39][40], as well as in harmonically trapped potential systems [41]. In addition, experimental evidence for VR has been reported in bistable and multistable vertical-cavity surface-emitting lasers (VCSELs) [19,22,42,43].…”
Section: Introductionmentioning
confidence: 99%